1992
DOI: 10.1116/1.586283
|View full text |Cite
|
Sign up to set email alerts
|

TiNxOy transparent electrode material for HgCdTe infrared devices

Abstract: We studied various transparent, conductive thin-film coatings for infrared focal-plane array applications. Films of TiNxOy prepared by reactive direct current magnetron sputtering best satisfied the performance and producibility requirements. The films have robust chemical and mechanical properties, little free-carrier absorptance, and the resistivity can be tailored to requirements. Transmission electron microscopy, x-ray diffraction, and x-ray photoelectron spectroscopy were used to study the film characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…They showed that the nitrogen content in the film increases as the growth temperature increases and films deposited on Si (100) exhibit a shift of diffraction peaks to higher Bragg angles. Nevertheless, potential applications of titanium oxynitride films as anti-reflecting coatings [14] and as optically selective absorbing coatings and transparent IR window electrodes [15,16], require further systematic investigations of the growth and the resulting properties of this material.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the nitrogen content in the film increases as the growth temperature increases and films deposited on Si (100) exhibit a shift of diffraction peaks to higher Bragg angles. Nevertheless, potential applications of titanium oxynitride films as anti-reflecting coatings [14] and as optically selective absorbing coatings and transparent IR window electrodes [15,16], require further systematic investigations of the growth and the resulting properties of this material.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Moreover, the presence of oxygen in titanium nitride films leads to a promising functional range of materials, TiN x O y , already used as solar selective absorbers, [5] or transparent windows for infrared detectors. [6,7] However, few works have been published on the growth, structure, and properties of these titanium oxynitride films. [8±12] Further, the electrical properties are almost unexplored, [8] although knowledge of the electrical behavior of such materials could lead to new applications.…”
Section: Introductionmentioning
confidence: 99%
“…TiN is widely used as a metallurgical coating for instance in cutting tools as a wear-resistant coating and as a diffusion barrier in large scale integrated circuits. There is also an increasing attention for titanium oxynitride coatings due to their interesting physical properties that lead to applications in optically selective absorbing films to enhance the contrast of cathode-ray tube displays [1], such as antireflection coatings [2], electrically switchable windows [3], transparent IR window electrodes [4], effective diffusion barriers for semiconductor applications [5] and as hard protective metallurgical coatings. It was also reported that such materials can promote in vivo formation of bone-like materials [6].…”
Section: Introductionmentioning
confidence: 99%